A Review on Pathophysiology, Clinical Manifestations, and Therapeutic Management of Non-Immune Hydrops Fetalis: Review Article (Journal of Pharma Insights and Research, 2025)
Non-immune hydrops fetalis (NIHF) is a fetal condition characterized by abnormal fluid accumulation in two or more anatomical compartments, including the peritoneal cavity, pleural space, pericardial sac, and subcutaneous tissues. While immune hydrops fetalis historically dominated cases due to maternal-fetal Rh incompatibility, the widespread implementation of anti-D immunoglobulin prophylaxis has led to NIHF becoming the predominant form, accounting for 85-95% of cases. The etiology of NIHF encompasses a broad spectrum of pathological conditions, including cardiovascular anomalies, chromosomal disorders, metabolic diseases, infections, and lymphatic malformations. Recent literature on prenatal diagnostic techniques, particularly genetic testing and high-resolution ultrasonography, have enhanced our ability to identify underlying causes and initiate appropriate interventions. The condition presents significant challenges in prenatal management and is associated with considerable perinatal morbidity and mortality rates. Treatment strategies vary based on the underlying etiology and may include intrauterine interventions, medical management, or early delivery in severe cases. Despite improved prenatal care and intervention options, the prognosis remains guarded, with survival rates varying significantly based on the underlying cause, gestational age at diagnosis, and severity of presentation. Long-term follow-up studies indicate that survivors may face various complications, emphasizing the need for comprehensive multidisciplinary care